Genetic diversity of wild, weedy and cultivated acccessions of Brassica rapa - Crouch, J.H.; Lewis, B.G.; Lydiate, D.J.; Mithen, R.F. (1995)
Restriction Fragment Length Polymorphisms (RFLPs) were used to study the genetic diversity within and between accessions of 'wild' and cultivated B. rapa. Two of the wild accessions were likely to be escapes from cultivation because of their geographical origins (Argentina and California). The nature of the other three wild accessions (from Turkey, Algeria and Sicily) was not known. Principal components analysis placed the Argentinian, Californian and Turkish accessions within a cluster which contained all the cultivated forms of B. rapa. The other two B. rapa accessions were genetically divergent and, on the basis of their RFLP genotypes, would have been considered to be more distant from the cultivated forms of B. rapa than accessions of B. nigra and B. montana. The implications of these results for germplasm conservation, selection of material for breeding programmes and phylogenetic studies on the origin of Brassica crops are discussed.